Pengaruh Baby Massage terhadap Kualitas Tidur Bayi Usia 3-6 Bulan di Babycare Bondowoso - Ucik Nurul Hidayati; Muthmainnah Zakiyyah; Bagus Supriyadi (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Infant sleep quality is a fundamental biological need that plays a crucial role in growth and neurological development; however, sleep disturbances remain common among infants aged 3-6 months and are often overlooked by parents. This condition poses risks to physical health, emotional well-being, and overall infant development. This study aims to analyze the effect of baby massage on sleep quality among infants aged 3-6 months at Babycare Bondowoso and to identify differences in sleep quality before and after the intervention. The study employed a quantitative approach with a quasi-experimental one-group pretest-posttest design involving 40 infants selected through total sampling. Data were collected using questionnaires and observation sheets, then analyzed using the Wilcoxon test. The results showed that prior to the intervention, 87.5% of infants experienced poor sleep quality, whereas after the intervention, all infants (100%) demonstrated improvement to good sleep quality. Statistical analysis indicated a p-value of 0.00, which is lower than 0.05, confirming a significant effect of baby massage on infant sleep quality. These findings demonstrate that baby massage effectively improves sleep duration, comfort, and stability through physiological relaxation mechanisms. The novelty of this study lies in providing empirical evidence of the effectiveness of baby massage as a non-pharmacological intervention that is simple, safe, and can be independently applied by parents while offering holistic benefits for infants. The findings are expected to serve as a basis for developing health education and improving infant care practices.